Extra intestinal manifestation of Crohn’s disease in a university teaching hospital, Nepal - Sharma, Yuba Raj (Journal of Patan Academy of Health Sciences, 2015)
Introductions: Crohn’s disease relatively uncommon gastrointestinal disease in Asia pacific region. There is increasing reports of this disease in the region. Aim of this study was analyze the demographics and extraintestinal manifestation of Crohn’s disease in tertiary care hospital setup in Nepal.Methods: This was a retrospective study of patients with Chron’s disease seen in gastroenterology unit of Patan Hospital from 2009 to 2014. Case records were analyzed for age, gender, geography and extra intestinal manifestations.Results: Eighteen patients with Crohn’s disease were identified, 13 male and five female. Age ranged from 14 to 70 years, with peak during 21-30 years. There were seven (39%) patients with extra intestinal manifestations of arthritis, aphthous ulcer in oral cavity, erythema nodosum and episcleritis in descending order.Conclusions: Threre were 18 cases in five years from in our tertiary care hospital and seven patients had extra intestinal presentation mainly arthritis and oral aphthous ulcer. Clinicians in Asian region need to be vigilant of Chron’s, once thought be the disease of developed countries.